PEMAHAMAN MUNASABAH SEBAGAI CABANG ULUMUL QUR’AN PASCA PROSES JAM’UL QUR’AN - Krisna Mukti Ragil Pamungkas; Putri Mandarisma; Rusyda Assyifa Dewi; Salma Ananda Nuraini; Tri Abna Br Meliala; Akhmad Dasuki (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Ulumul Qur’an is a field of knowledge that discusses the Qur’an, including its history such as how it was compiled, written, the reasons for its revelation, whether it is Makkiyah or Madaniyah, as well as abrogation Naskh-Mansukh. This field of knowledge also covers understanding Qira’ah al-Qur’ān, I’jaz Al-Qur’an, al- Munasabah, al-Muhkamat and al-Mutashabihat, translation, Tafsīr, Ta`wīl, and various methods of interpreting the Al-Qur’an. This article aims to discuss one branch of Ulumul Qur’an, namely Munasabah, systematically and describe it in terms of cause and effect relationships, specifications, explanations, reinforcement, comparison, or other aspects that connect one verse with another. Munasabah is one branch of Ulumul Qur’an that is very necessary for understanding the content or meaning contained in the Al- Qur’an. This research uses the literature study method, which is a technique for collecting data or information by reading articles, journals, and books to be reviewed. The importance of understanding the relationship between verses of the Al-Qur’an in religious life makes the author interested in analyzing Munasabah in order to be beneficial, especially in daily life. Therefore, understanding the role of Munasabah is very important for Muslims to gain a deep comprehension of the chronological meanings contained in the Al-Qur’an.